This is a file in the archives of the Stanford Encyclopedia of Philosophy. |
Proof.
If E
F, then as we observed earlier, Ki(E)
Ki(F), so
K 1N ( E ) = ![]()
iN
K i( E ) = ![]()
iN
Ki(F) = K1N(F)
If we now set
E
=
KnN(E) and
F
=
KnN(F), then by the argument just given we have
Kn+1N(E) = K1N(E )
K1N(F
) = Kn+1N(F)
so we have mth level mutual knowledge for every
n 1.
Hence if ![]() ![]() |
![]() ![]() n = 1 |
KnN(E) then
![]() ![]() |
![]() ![]() n = 1 |
KnN(F). ![]() |
Peter Vanderschraaf peterv@MAIL1.ANDREW.CMU.EDU |